EVALUASI KERAPATAN JARINGAN STASIUN HUJAN DI DAS BOLANGO BONE - Laude, Evita Verent; Labdul, Barry Yusuf; Husnan, Rawiyah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2023)
The location and number of rain stations in a watershed area are the main components in ensuring the availability of rainfall data. Evaluation of the rain station network density is needed to determine the condition of the distribution of rain stations and new rain stations recommendation. The research was conducted in the Bolango Bone watershed with 10 existing rain stations. Rainfall observation data in 7 years (2013-2019). The location and number of rain stations were analyzed using the Kagan-Rodda method based on the standards set by the WMO (World Meteorological Organization) of 100-250 km2/station. The result of the Kagan Method is the optimal number and pattern of placement of rain stations. The evaluation results from 10 stations in the Bolango Bone watershed showed that there were 3 stations, namely Pangi, Pinogu, and Sukamakmur, which did not meet the density of rain stations suggested by WMO. The correlation coefficient for monthly rainfall ranged from 0.4238-0.8351. This correlation value was the average of all rain stations in the Bolango Bone watershed. Based on the results of the Kagan-Rodda analysis, two recommendations were obtained. The first recommendation is to maintain the existing 10 stations with an average error Z1 = 4.12%, interpolation error Z2 = 9.24%, and the distance between stations l = 14.58 km, repositioning the rain stations to each vertex of the Kagan-Rodda triangle. The second recommendation is to add 4 new rain stations without repositioning the existing 10 rain stations with an average error Z1 = 3.45%, interpolation error Z2 = 8.93%, and distance between stations l = 12.32 km.